MODIFIKASIb 3-Pyropheophorbide α MENGGUNAKAN ATOM PUSAT Mg dan Ca SEBAGAI SENSITIZER PADA DYE SENSITIZED SOLAR CELL (DSSC) DENGAN METODE KOMPUTASI - Sekar Dian Fitriyani, NIM.: 20106030043 (2025)
The efficiency of natural dyes as sensitizers in Dye-Sensitized Solar Cells (DSSC) such as pyropheophorbide α is still limited. This study aims to improve the photoelectric properties of the compound 3-Pyropheophorbide α (3-PPhe-α) modified by the addition of Magnesium (Mg) and Calcium (Ca) central atoms as sensitizers in Dye-Sensitized Solar Cells (DSSC). The results of the study were compared with the 3-PPhe-α compound without modification based on photoelectric property parameters, including HOMO-LUMO energy, UV-Vis absorption, |VRP|, ΔGinject, τ, LHE, and FEDAM analysis. Geometry optimization was performed using Avogadro and Orca 4.2.1 software with a 6-311G** basis set and LANL2DZ for Mg and Ca central atoms. Interpretation of the results was performed using Avogadro, Chemissian, and GaussSum software. The calculation results show that modification with Mg and Ca increases the spontaneity of electron injection with the most negative ΔGinject value (-3.776 eV), while Ca extends the excited state lifetime to 0.180 ns. UV-Vis spectrum analysis shows hypsochromic and bathochromic shifts in both modified molecules. The hypsochromic shift causes the LHE values of 3-Mg-PPhe-α and 3-Ca-PPhe-α to be lower than 3-PPhe-α.